Total spondylectomy of recurrent giant cell tumors in the cervical spine: Two case reports and review of literature. Issue 20 (May 2018) - Tu, Ji; Li, Wentian; Shu, Shenglei; Zhang, Yukun; Hua, Wenbin; Li, Shuai; Yang, Shuhua; Yang, Cao
Abstract: Rationale: Spinal Giant Cell Tumors (SGCTs) are rare, aggressive, and benign tumors. Their presence in the cervical spine is even more exceptional. There are few reports of cervical GCT in the literature, especially recurrent cases. The treatment are challenging to clinically because radical resection is extremely difficult. Patient concerns: In this study, we present the cases of a 25-year-old man and a 41-year-old woman who suffered from recurrent cervical GCT. Interventions: They underwent extensive total spondylectomy of C3-5 and C2-4, respectively, by a combined anterior and posterior approach. Outcomes: Both patients had a satisfactory prognosis after 2 years followe-up, and extensive total spondylectomy provided good disease-free survival rates. Extensive total spondylectomy of cervical recurrent giant cell tumor was successfully achieved combined anterior and posterior approach. Lessons: This surgical technique can be an effective option for this pathological condition, which is difficult to manage using other conventional treatment options including repeated curettage and radiotherapy. However, there are insufficient data on long-term subjective outcomes in this type of patient, and larger series studies are needed to determine the efficacy of this approach, especially compared with piecemeal resection techniques.